Pembinaan Asrama Sebagai Bagian Pendidikan Karakter Yang Berlandaskan Alkitab di LKSA Sekar Pengharapan Bali - Ni Nyoman Fransiska; Gusti Ngurah Sukadana; I Gusti Ayu Oka Mahadewi (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This research arises from the urgent need to develop a comprehensive coaching model for children in vulnerable situations. Through an integrative approach based on biblical values, this research aims to transform the paradigm of coaching children in social institutions, focusing on the formation of a whole and dignified character. The research team used a qualitative method with a participatory descriptive approach, which places lectures and active discussions as the main instruments of data collection and processing. The research design was designed to explore the dynamics of character development at LKSA Sekar Pengharapan through direct and reflective interactions. The research proved the effectiveness of the Bible-based character development approach in transforming the lives of children at LKSA Sekar Pengharapan. The model developed is not merely theoretical, but has practical significance in breaking the chain of social problems and building a generation of character.